2013
DOI: 10.1016/j.bcp.2013.08.067
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of ibuprofenoyl-CoA and other 2-APA-CoA esters by human acyl-CoA thioesterases-1 and -2 and their possible role in the chiral inversion of profens

Abstract: Ibuprofen and related 2-arylpropanoic acid (2-APA) drugs are often given as a racemic mixture and the R-enantiomers undergo activation in vivo by metabolic chiral inversion. The chiral inversion pathway consists of conversion of the drug to the coenzyme A ester (by an acyl-CoA synthetase) followed by chiral inversion by α-methylacyl-CoA racemase (AMACR; P504S). The enzymes responsible for hydrolysis of the product S-2-APA-CoA ester to the active S-2-APA drug have not been identified. In this study, conversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Both ACOT1 and ACOT2 can effectively hydrolyze a variety of 2-APA-CoA substrates. ACOT1 can hydrolyze 2-APA-CoA esters outputted from mitochondria and peroxisomes, thereby suppressing cyclo-oxygenase (COX) -1 and -2 in the endoplasmic reticulum, while ACOT2 can regulate 2-APA toxicity and mitochondrial free CoA levels [ 56 ]. St Clair et al [ 57 ] found that ACOT, as a rheostat controlling activated fatty acid, has a regulatory effect on the replication of dengue virus serotype 2 (DENV2) and the release of infectious particles.…”
Section: Discussionmentioning
confidence: 99%
“…Both ACOT1 and ACOT2 can effectively hydrolyze a variety of 2-APA-CoA substrates. ACOT1 can hydrolyze 2-APA-CoA esters outputted from mitochondria and peroxisomes, thereby suppressing cyclo-oxygenase (COX) -1 and -2 in the endoplasmic reticulum, while ACOT2 can regulate 2-APA toxicity and mitochondrial free CoA levels [ 56 ]. St Clair et al [ 57 ] found that ACOT, as a rheostat controlling activated fatty acid, has a regulatory effect on the replication of dengue virus serotype 2 (DENV2) and the release of infectious particles.…”
Section: Discussionmentioning
confidence: 99%
“…The organism processing of ibuprofen reduces the normal activity of AMACR, which could reduce cancer developing. Although this mechanism study is still not conclusive, it is an interesting subject of study because AMACR is used as a marker (P504S) for several types of cancers 25,26 .…”
Section: Ibuprofen: Biological Activities and Applications In Medicinementioning
confidence: 95%